To 70 years of Institute of Plant Protection of NAAS of Ukraine. The development of phytopathological investigations - Krut , M.V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
In the article is shown the history of scientific investigations of Institute of Plant Protection of National Academy of Agrarian Sciences of Ukraine in the field of phytopathology during 70 years of its activity. The names of leading scientists-phytopathologists are given.